Keefektifan Pemanfaatan dan Arah Pengembangan Laboratorium Prestasi dan Kondisi Fisik FIK UNY - Riky Dwihandaka; Sumarjo Sumarjo (YLPK Mahardhika, 2020)
This study aims to reveal the effectiveness of utilization and to find out the direction of laboratory development of achievement and physical conditions in the Faculty of Sports Science, which consists of the level of use and completeness of laboratory infrastructure, laboratory management skills, managerial abilities, individual abilities, and student attitudes towards the direction of laboratory development. This research is a qualitative research. The qualitative data collection method used is the data triangulation method which consists of: 1) Focus group discussion (FGD) for students (6 people/group), and 2) Non-participant observation in laboratory settings. The population of this study were all odd semester students who used the achievement laboratory and the physical condition of FIK UNY. The number of samples is based on the saturation of themes in focus group discussions and in-depth interviews. The sample selection of students was carried out based on convenience sampling technique, while in-depth interviews with laboratory managers used criterion sampling techniques. Data analysis used three stages consisting of: 1) data reduction, 2) reconstructive data and 3) thematic analysis. Based on the research that has been done, the results show that FIK UNY students feel that the existence of an achievement laboratory and physical condition is very useful both in its use in lectures, training and research. In increasing the use of laboratory facilities, performance and physical conditions are emphasized on their use, management, maintenance and maintenance. Laboratory achievements need to be promoted and for laboratories in physical condition, staff or laboratory personnel need to be added. The development of performance laboratories and physical conditions is directed towards maintenance and maintenance as well as the construction of a wider and more integrated building. Key words: utilization, development, laboratory Penelitian ini bertujuan untuk mengungkapkan keefektifan pemanfaatan dan mengetahui arah pengembangan laboratorium prestasi dan kondisi fisik di Fakultas Ilmu Keolahragaan, yang terdiri dari tingkat penggunaan dan kelengkapan sarana prasarana laboratorium, kemampuan pengelolaan laboratorium, kemampuan manajerial, kemampuan individual, dan sikap mahasiswa terhadap arah pengembangan laboratorium. Penelitian ini merupakan penelitian kualitatif. Metode pengumpulan data kualitatif yang dipergunakan adalah metode triangulasi data yang terdiri dari :1) Focus group discusion (FGD) pada mahasiswa (6 orang/kelompok), dan 2) Observasi non-participant pada setting laboratorium. Populasi penelitian ini adalah seluruh mahasiswa semester gasal yang menggunakan laboratorium prestasi dan kondisi fisik FIK UNY. Jumlah sampel didasarkan pada saturasi tema pada focus group discussion maupun in-depth interview. Pemilihan sampel pada mahasiswa dilakukan berdasarkan teknik convenience sampling sedangkan pada in-depth interview dengan pengelola laboratorium dengan mempergunakan teknik criterion sampling. Analisis data menggunakan tiga tahap terdiri dari: 1) data reduction, 2) data reconstrucsi dan 3) analisis thematic. Berdasarkan penelitian yang telah dilakukan diperoleh hasil bahwa mahasiswa FIK UNY merasa keberadaan laboratorium prestasi dan kondisi fisik sangat bermanfaat baik dalam penggunaannya dalam kuliah, latihan maupun penelitian. Dalam meningkatkan penggunaan sarana laboratorium prestasi dan kondisi fisik ditekankan pada pemakaian, pengelolaan, perawatan dan pemeliharaannya. Laboratorium prestasi perlu ditingkatkan promosinya dan untuk laboratorium kondisi fisik perlu ditambahkan staf atau petugas tenaga laboratorium. Pengembangan laboratorium prestasi dan kondisi fisik diarahkan dalam pemeliharaan dan perawatan serta pembuatan gedung yang lebih luas dan terpadu. Kata kunci: pemanfaatan, pengembangan, laboratorium